Sick sinus syndrome as a late complication after ventricular septal defect surgery - Sakai, Chieko (J Cardiol Cases, 2013)
Ventricular septal defect is a common congenital heart disease for which patch closure technique using cardiopulmonary bypass has been applied for a few decades, resulting in a low incidence of perioperative complications. We report a 26-year-old woman with bradycardia of 25–30 beats per minute, which was considered to be a late-onset complication of surgical closure of an isolated ventricular septal defect performed 21 years earlier. She has been stable for more than 9 months without an implanted pacemaker, although her heart rate was always around 40 beats per minute in scheduled follow-up visits. <Learning objective: We experienced a 26-year-old woman with bradycardia of 25–30 beats per minute, which was considered to be a late-onset complication of surgical closure of an isolated ventricular septal defect performed 21 years earlier. Our case highlights the importance of close follow-up for patients who underwent successful surgical closure of a ventricular septal defect and have shown nonsignificant bradycardia, even though they have no symptoms.>